Surface modification of COC : study of surface morphology and cell adhesion - Ho, Hedi Ying Ci. (2011)
Microfluidic devices play an important role in many applications today with its ‘lab-on-chip’ technology. The study of microfluidic devices entails the precise control of fluids at microscale which gives rise to many added advantages.